Serum sPD1 and sPDL1 as Biomarkers for Evaluating the Immune State of Lung Adenocarcinoma Patients - Yumin Wu; Hui Guo; Jiawei Yue; Peng Xu (Journal of Immunology Research)
A large proportion of cancer patients benefit from immune checkpoint therapy, while few studies focused on the relationship between soluble PD1 (sPD1) and soluble PDL1 (sPDL1) in serum and immune status of patients. ILC2 and M2 were confirmed to be related to immunosuppression in tumor patients. To determine whether sPD1 and sPDL1 are correlated with the ratio of ILC2 and M2 is helpful to explore the possibility of using sPD1 and sPDL1 as tumor molecular markers. Our results showed an immune balance toward ILC2 and M2-like monocytes in patients with LUAD compared with healthy controls. Meanwhile, decreased CD4+T and CD8+T cells, as well as elevated PD1+CD8+T cells, were found in patients with LUAD. The relative mRNA expression levels of ILC2- and M2-characteristic cytokines were also upregulated accompanied by decreased mRNA expression levels of ILC1- and M1-characteristic cytokines in patients with LUAD compared to healthy controls. Moreover, elevated ILC2 frequencies as well as the amount of IL-13 were positively correlated with the amount of sPD1, however, there was no correlation between them and sPDL1. These results suggested that sPD1 and sPDL1 can serve as diagnostic markers to predict the immune state of cancer patients.